An introduction to formal languages and automata - Linz, Peter (Jones & Bartlett Learning, 2012)
In the new Fifth Edition, Peter Linz continues to offer a straightforward, uncomplicated treatment of formal languages and automata and avoids excessive mathematical detail so that students may focus on and understand the underlying principles. In an effort to further the accessibility and comprehension of the text, the author has added new illustrative examples and exercises throughout.